Advancing outdoor education: The validation of Adventure-based Mental Toughness Model (AbMTM) - Mohd Shariman Shafie; Md Amin Md Taff; Zuraidah Zainol; Siti Musliha Mat Rasid; Mustakim Hashim; Omar Firdaus Mohd Said; Mohd Noorazlan Ab Aziz; Mohamed Azizul Mohamed Afandi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
In Malaysia, the implementation of physical education includes an outdoor education syllabus. Outdoor education is found to be a medium for individual development at various levels of educational institutions, including schools. Mental toughness is one of the major aspects of the psychological development of an individual. There are now numerous studies linking mental toughness with academic performance. One of the mediums for this development is the implementation of outdoor education. The nature of outdoor education is found to have a very high potential to support the development of mental toughness among students. However, a lack of specific adventure-based mental toughness models has been developed. This study attempted to develop the Adventure-based Mental Toughness Model (AbMTM) and was guided based on the modified Design and Development Research (Saedah, Muhammad, & Rozaine, 2020). A total of 507 (N=507) respondents from several educational institutions in Malaysia were involved as respondents for the validity examination through the Structural Equation Modelling (SEM) approach. As a result, AbMTM recorded significant Goodness of Fit (GoF) (X2= 1.904; p =.000; GFI=.839; AGFI=.792; NFI=.815; TLI=.924; CFI=.931; RMSEA= .050). This study’s findings are considered a new horizon of outdoor education implementation and advancing the current practice in Malaysia. Keywords: Outdoor education, mental toughness, structural equation modeling